The effect of load and technique on biomechanical and psychophysical responses to level dynamic pushing and pulling - Bennett, Anthea Iona (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2009)
Pushing and pulling research has yet to fully elucidate the demands placed on manual workers despite established epidemiological links to musculoskeletal disorders. The current study therefore aimed to quantify biomechanical and perceptual responses of male operators to dynamic pushing and pulling tasks. Three common push/pull techniques (pushing, one handed and two handed pulling) were performed at loads of 250kg and 500kg using an industrial pallet jack in a laboratory environment. Thirty six healthy male subjects (age: 21 ±2 years, stature: 1791 ±43 mm and body mass: 77 ±10 kg) were required to perform six loaded experimental and two unloaded control conditions. Hand force exertion, muscle activity and gait pattern responses were collected during 10m push/pull trials on a coefficient controlled walkway; body discomfort was assessed on completion of the condition. Horizontal hand force responses were significantly (p<0.05) affected by load, with a linear relationship existing between the two. This relationship is determined by specific environmental and trolley factors and is context specific, depending on factors such as trolley maintenance and type of flooring. Hand force exertion responses were tenuously affected by technique at higher loads in the initial and sustained phases, with pushing inducing the greatest hand forces. Comparison of the motion phases revealed significant differences between all three phases, with the initial phase evidencing the greatest hand forces. Muscle activity responses demonstrated that unloaded backward walking evoked significantly higher muscle activation than did unloaded forward walking whilst increased muscular activity during load movement compared to unloaded walking was observed. However increasing load from 250kg to 500kg did not significantly impact the majority of muscle activity responses. When considering technique effects on muscle activity, of the significant differences found, all indicated that pushing imposed the least demand on the musculoskeletal system. Gait pattern responses were not significantly affected by load/technique combinations and were similar to those elicited during normal, unloaded walking. Perceptually, increased load led to increased perception of discomfort while pushing resulted in the least discomfort at both loads. From these psychophysical responses, the calves, shoulders and biceps were identified as areas of potential musculoskeletal injury, particularly during one and two handed pulling. Pushing elicited the highest hand forces and the lowest muscle activity responses in the majority of the conditions whilst psychophysical responses identified this technique as most satisfactory. Current results advocate the use of pushing when moving a load using a wheeled device. Suitability of one and two handed pulling remains contradictory, however results suggest that one handed pulling be employed at lower loads and two handed pulling at higher loads.
Keywords: Work -- Physiological aspects; Human engineering -- Case studies; Lifting and carrying -- Case studies; Biomechanics -- Case studies; Musculoskeletal system -- Wounds and injuries